CEP164 Deficiency Causes Hyperproliferation of Pancreatic Cancer Cells - Kobayashi, Tetsuo; Tanaka, Kosuke; Mashima, Yu; Shoda, Ayano; Tokuda, Mio; Itoh, Hiroshi (Frontiers in Cell and Developmental Biology, 2020)
Primary cilia are hair-like projections that protrude from most mammalian cells and mediate various extracellular signaling pathways. Pancreatic ductal adenocarcinoma (PDAC) cells are known to lose their primary cilia, but the relevance of this phenomenon remains unclear. In this study, we generated PDAC-originated Panc1 cells devoid of primary cilia by mutating a centriolar protein, CEP164, which is required for ciliogenesis. CEP164 depletion enhanced the clonogenicity of Panc1 cells, along with chemically-induced elimination of primary cilia, suggesting that a lack of these organelles promotes PDAC cells proliferation. In addition, the loss of CEP164 altered the cell cycle progression irrespective of absence of primary cilia. We found that CEP164 was co-localized with the GLI2 transcription factor at the mother centriole and controlled its activation, thus inducing Cyclin D-CDK6 expression. Furthermore, CEP164-mutated Panc1 cells were significantly tolerant to KRAS depletion-dependent growth inhibition. This study suggests that CEP164 deficiency is advantageous for PDAC cells proliferation due to not only lack of ciliation but also cilia-independent GLI2-Cyclin D/CDK6 activation, and that CEP164 is a potential therapeutic target for PDAC.